Complete Sequence of the First Chimera Genome Constructed by Cloning the Whole Genome of Synechocystis Strain PCC6803 into the Bacillus subtilis 168 Genome - Watanabe, Satoru (American Society for Microbiology, 2012)
Genome synthesis of existing or designed genomes is made feasible by the first successful cloning of a cyanobacterium, Synechocystis PCC6803, in Gram-positive, endospore-forming Bacillus subtilis. Whole-genome sequence analysis of the isolate and parental B. subtilis strains provides clues for identifying single nucleotide polymorphisms (SNPs) in the 2 complete bacterial genomes in one cell.